Review of Laura I. Rendón’s “Sentipensante (Seeing/Thinking) Pedagogy: Educating for Wholeness, Social Justice, and Liberation” - Worthington, Natasha (My University, 2016)
In her book, Sentipensante (Sensing/Thinking) Pedagogy: Educating for Wholeness, Social Justice, and Liberation, author, educator, and Fetzer Institute Fellowship alumnus Laura I. Rendón lays the framework and provides the rationalization for the need for higher education professionals to embrace and integrate the concepts of “wholeness, consonance, social justice, and liberation” in teaching and learning.
Keywords: Book review; Pedagogy